Comparative Evaluation of Whole Body and Hepatic Insulin Resistance Using Indices from Oral Glucose Tolerance Test in Morbidly Obese Subjects with Nonalcoholic Fatty Liver Disease - Kamran Qureshi; Ronald H. Clements; Fahad Saeed; Gary A. Abrams (Journal of Obesity)
Nonalcoholic Fatty Liver Disease (NAFLD) is the hepatic manifestation of metabolic syndrome and is a marker of Insulin Resistance (IR). Euglycemic-hyperinsulinemic clamp is the gold standard for measuring whole body IR (hepatic + peripheral IR). However, it is an invasive and expensive procedure. Homeostasis Model Assessment Index for Insulin Sensitivity (HOMA-IS), Quantitative Insulin Sensitivity Check Index (QUICKI) for hepatic IR and Insulin Sensitivity Index (ISI0,120), and Whole Body Insulin Sensitivity Index (WBISI) for whole body IR are the indices calculated after Oral Glucose Tolerance Test (OGTT). We used these indices as noninvasive methods of IR (inverse of insulin sensitivity) estimation and compared hepatic/peripheral components of whole body IR in NAFLD. Methods. 113 morbidly obese, nondiabetic subjects who underwent gastric bypass surgery and intraoperative liver biopsy were included in the study. OGTT was performed preoperatively and the indices were calculated. Subjects were divided into closely matched groups as normal, fatty liver (FL) and Non-Alcoholic Steatohepatitis (NASH) based on histology. Results. Whole body IR was significantly higher in both FL and NASH groups (NAFLD) as compared to Normal, while hepatic IR was higher only in NASH from Normal. Conclusions. FL is a manifestation of peripheral IR but not hepatic IR.